A quad-port multiple-input-multiple-output system for underlay or interweave cognitive radio - Laith Wajeeh Abdullah; Qasim Hadi Kareem; Adheed Hasan Sallomi (Institute of Advanced Engineering and Science, 2023)
This paper presents a four-element frequency reconfigurable antenna system that is novel in terms of gathering both underlay and interweave cognitive radio in a single multiple input, multiple output (MIMO) design. Built on a 50×38×0.8 mm3 Rogers RT/Duroid 5880 substrate, this system is constructed of two scanning elements to sense ultra-wide band (UWB) with controllable band notching capabilities and two elements act as communication antennas. Eighteen MIMO modes can be provided depending on the state of the five positive-intrinsic-negative (PIN) diodes in each sensing antenna and the four PIN diodes in each communication antenna. These include a scanning UWB mode, fourteen modes to notch WiMax/Cband/wireless local area network (WLAN)/Xband/ITU in single/dual/triple/quad band rejection states and three interweave modes where each targeting one of the regions of WiMax/Cband/WLAN. Simulated by CST v.10; results like input reflection coefficient and realized gain verify system's capability to work in each operation mode. Moreover, mutual coupling, envelope correlation coefficient and diversity gain all evidence the performance of the proposed system as a MIMO system. Results, simple and compact profile, wide and flexile range of MIMO operation modes in line with the novelty to handle both underlay and interweave cognitive radio all nominate this system as promising to fulfill the needs of modern wireless communications.